Pre-School Teachers’ Views on the Impact of Visual Arts Education on Early Childhood Education - Vasilaki, Vasiliki (Innovare Journal of Education, 2024)
The current study explores the impact of visual arts education on early childhood, highlighting its role in enhancing creativity, imagination, and emotional expression in pre-school children. It explores the perspectives of pre-school teachers on the importance of visual arts in children’s development and the challenges they face when integrating the arts into the curriculum. The study used quantitative and qualitative research methods. The study highlights how pre-school educators value the visual arts for its potential to enhance cognitive and social skills and how demographic factors influence these perceptions. In addition, it explores the practical aspects of art education, including classroom management and resource allocation, to offer a comprehensive view of the current state and future potential of visual arts in early childhood education. Finally, this research contributes to a deeper understanding of the central role of the visual arts in early education. It highlights the need for supportive educational policies and resources to enrich the learning environment.